(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This work presents an analysis of the use of the Balanced Scorecard (BSC) as a strategic management tool and performance control in family businesses. Today companies compete in complex environments, so a perfect understanding of their goals and methods to achieve them is essential. The Balanced Scorecard translates the mission and strategy of companies into a comprehensive set of performance measures that serve as the basis for a strategic measurement and management system. The Balanced Scorecard measures organizational performance from four balanced perspectives: financial, customer, company internal processes, and learning and growth.